1992
DOI: 10.1172/jci116028
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa cell-derived insulin-like growth factor (IGF) binding proteins are inhibitory to IGF-I hormonal action. Evidence derived from the use of a truncated IGF-I analogue.

Abstract: An increasing body of information now suggests that insulinlike growth factor (IGF) binding proteins (BPs) may serve as antigonadotropins at the level of the ovary. It is the objective of the present communication to evaluate the functional role of endogenous (granulosa cell-derived) IGFBPs by exploiting the unique properties of des(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…The corresponding IGFBP profiles for the two pools of follicular fluid from healthy (lane a) and atretic (lane b) follicles are shown in Figure 3b. In similar experi ments, Adashi et al [33] showed that in vitro, des(l-3)IGF-1 which has a weak affinity for IGFBPs is more potent than IGF-I in promoting the FSH-stimulated accu mulation of progesterone by rat granulosa cells in IGFBP-5-replete circumstances, whereas both peptides are equipotent in IGFBP-5-deplete circumstances.…”
Section: Consequences On the Bioavailability Of Igfs At The Level Of mentioning
confidence: 83%
“…The corresponding IGFBP profiles for the two pools of follicular fluid from healthy (lane a) and atretic (lane b) follicles are shown in Figure 3b. In similar experi ments, Adashi et al [33] showed that in vitro, des(l-3)IGF-1 which has a weak affinity for IGFBPs is more potent than IGF-I in promoting the FSH-stimulated accu mulation of progesterone by rat granulosa cells in IGFBP-5-replete circumstances, whereas both peptides are equipotent in IGFBP-5-deplete circumstances.…”
Section: Consequences On the Bioavailability Of Igfs At The Level Of mentioning
confidence: 83%
“…IGFBP modulates IGF action in the cell environment, inhibiting or enhancing its activity (17)(18)(19)(20). The inhibitory effects of IGFBP have been attributed to competitive scavenging of IGF peptides from the IGF-1R (42).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1, MMP-2, and MMP-3 degrade and , and TIMP-1 inhibits proteolytic cleavage of IGFBP-3 in rat pregnant serum (16). IGFBP proteolysis may represent a mechanism for tissue-specific regulation of IGF bioavailability, either inhibiting and/or enhancing IGF activity in many cell types (17)(18)(19)(20).Identification of new hST-3 substrates is a necessary step for the understanding of its physiological relevance. To date, hST-3 proteolytic activity has been described only for the nonspecific MMP substrates ␤-casein and ␣ 2 -macroglobulin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The IGFBPs can therefore be considered to play a critical role in modifying the biological actions of IGFs. In the ovary, only inhibitory actions of IGFBPs on follicular function have been demonstrated to date [12][13][14][15][16], Exogenously administered IGFBP-2 and -3 were reported to inhibit FSH-stimulated estradiol and progesterone production in cultured rat granulosa cells [12]. In the rat ovary, the mRNAs for IGFBP-2, IGFBP-3 and IGFBP-4 were shown to be selectively expressed in the interstial cells, copora lutea and granulosa cells of atretic follicles, respectively [17,18].…”
mentioning
confidence: 99%